A new Euler-Lagrangian cavitation model for tip-vortex cavitation with the effect of non-condensable gas. (January 2021) - Cheng, Huaiyu; Long, Xinping; Ji, Bin; Peng, Xiaoxing; Farhat, Mohamed
Highlights: The cavitating flow around a tip vortex is simulated with LES. The reason for the discrepancy between the predicted and observed TVC is discussed. An Euler-Lagrangian cavitation model is proposed to improve the accuracy of TVC. Abstract: Numerical simulation of tip vortex cavitation (TVC) remains a challenging task in a variety of applications, such as axial turbines and pumps as well as marine propellers. Although it is well known that TVC is highly sensitive to gas content, be it dissolved or not, numerical models do not consider this aspect so far. As a result, numerical simulations usually underestimate the development or the intensity of TVC. In the present paper, we propose an new Euler-Lagrangian cavitation model based on Rayleigh-Plesset (R-P) equation, taking into account the non-condensable gas. In this model, the Euler method is used to solve the global flow field and the Lagrangian method is used to track the migration of non-condensable gas bubbles into the vortex core. Based on the simplified R-P equation, the connection between local gas concentration and its effect on cavitation is modeled and the mass source terms in the original Schnerr-Sauer (S-S) cavitation model are modified. We applied the new cavitation model to a simplified case study, made of an elliptical NACA-16020 hydrofoil and compared the results with experimental observation. We obtained a significant improvement of the TVC prediction. Our work illustrates the major role of the gas content in sustaining cavitation downstream of the hydrofoil through an efficient attraction of nuclei, fueled by the low pressure induced by the vortex flow.